2020
DOI: 10.5897/ajfs2020.1929
|View full text |Cite
|
Sign up to set email alerts
|

Food safety knowledge and practices of street food vendors in selected locations within Kiambu County, Kenya

Abstract: The safety of street foods remains a public health concern especially in developing countries like Kenya where foodborne illnesses associated with these foods have often been reported. This study determined the food hygiene and safety knowledge and practices of 345 street food vendors (SFVs) in selected locations within Kiambu County, Kenya. Data collection was accomplished through face-toface interviews using structured questionnaires and extensive observation using an assessment tool for observation of perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
2
12
1
Order By: Relevance
“…Vendors who were inspected by health professionals were more likely to have appropriate food hygiene practices than those who were not. A study conducted in some parts of Ethiopia like in Gondar 38 and Arba Minch town 39 as well in Kiambu County of Kenya 10 were agreed with this finding. Furthermore, not only this study on street food vendors, but also a study conducted in Northwestern Ethiopia at some hotels and restaurants discovered that a lack of regular expert inspection was recognized as a determinant factor of food hygienic practices.…”
Section: Discussionsupporting
confidence: 66%
“…Vendors who were inspected by health professionals were more likely to have appropriate food hygiene practices than those who were not. A study conducted in some parts of Ethiopia like in Gondar 38 and Arba Minch town 39 as well in Kiambu County of Kenya 10 were agreed with this finding. Furthermore, not only this study on street food vendors, but also a study conducted in Northwestern Ethiopia at some hotels and restaurants discovered that a lack of regular expert inspection was recognized as a determinant factor of food hygienic practices.…”
Section: Discussionsupporting
confidence: 66%
“…Trafiałek et al [54] report similar results. The reason for better hygienic conditions in Poland may be better general education of street food vendors than in developing countries, where only a small percentage of vendors have secondary education and the rest have primary or lower education [7,52,53,65,67,129]. However, some authors suggest that it is not the level of education, but rather training and licensing, that have the effect of increasing food safety knowledge and improving food handling practices [56].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that the food safety hazard awareness and handling practices among African informal food vendors are poor (Mwove et al., 2020; Letuka et al., 2021; Oladipo‐Adekeye & Tabit, 2021; Azanaw et al., 2022). As was observed in Kenya, Ethiopia and South Africa, inadequate food safety knowledge is a determining factor in the poor handling practices of informal food vendors (Letuka et al., 2021; Nkosi & Tabit, 2021; Azanaw et al., 2022).…”
Section: Risk Factors Exacerbating L Monocytogenes Consumer Exposure ...mentioning
confidence: 99%
“…A survey of street food vendors in Johannesburg, South Africa found that at least 60% of them did not know the correct temperature for the hot and cold storage of RTE foods (Oladipo‐Adekeye & Tabit, 2021). In Kenya, a similar survey found that foods requiring refrigeration are frequently kept at ambient temperatures by almost 80% of street vendors (Mwove et al., 2020). Moreover, many vendors keep leftover foods for sale on the following day, sometimes without any form of preservation (Mwove et al., 2020).…”
Section: Risk Factors Exacerbating L Monocytogenes Consumer Exposure ...mentioning
confidence: 99%